Prominent Expression of Two Forms of Glutamate Decarboxylase in the Embryonic and Early Postnatal Rat Hippocampal Formation - Dupuy, Shannon T. (J Neurosci, 1996)
Immunohistochemical methods were used to determine the earliest times of detection for two forms of glutamate decarboxylase (GAD67 and GAD65) in the embryonic and early postnatal rat hippocampal formation and to determine whether their distribution patterns differed from each other and from those of the adult. Both GAD67- and GAD65-containing neurons were observed as early as embryonic day 17 (E17)–E18 in the hippocampus and E19 in the dentate gyrus, and this was substantially earlier than GAD had been detected previously in the hippocampal formation. The two GAD isoforms displayed very similar distribution patterns, but these patterns were distinctly different from those of the adult. From E17 to E20, GAD67 and GAD65 were expressed in neuronal cell bodies throughout the hippocampal and dentate marginal zones (future dendritic layers), and relatively few existed within the principal cell body layers, where GAD-positive neurons are frequently concentrated in the adult. At E21 to postnatal day 1 (P1), there was a sudden shift from a predominance of GAD-containing cell bodies within the developing dendritic regions to a meshwork of GAD-positive processes with terminal-like varicosities in these same regions. This pattern also contrasted with that of the adult, in which GAD-labeled terminals are highly concentrated in the principal cell layers. Electron microscopic observations of the GAD-labeled processes at P1 confirmed their axon-like appearance and demonstrated that the immunoreactivity was consistently localized in vesicle-filled regions that were often closely apposed to and, in some instances, established synaptic contacts with dendritic profiles. The present identification of an early abundance of GAD-containing structures in the hippocampal formation and the marked change in their distribution during development complement recent observations of developmental changes in the functioning of the GABA system and provide additional support for the early involvement of this neurotransmitter system in hippocampal development.